2020
DOI: 10.3390/rs12152364
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Never-Never Land: Integrating LiDAR and Geophysical Surveys at the Johnston Site, Pinson Mounds State Archaeological Park, Tennessee, USA

Abstract: Archaeologists often use near-surface geophysics or LiDAR-derived topographic imagery in their research. However, rarely are the two integrated in a way that offers a robust understanding of the complex historical palimpsests embedded within a social landscape. In this paper we present an integrated aerial and terrestrial remote sensing program at the Johnston Site, part of the larger Pinson Mounds landscape in the American MidSouth. Our work at Johnston was focused on better understanding the history of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Our approach to the survey area was explicitly multi-scalar and multi-method, with hopes of being able to disentangle some of the palimpsestic [102][103][104] evidence for social change at Cahokia. Such approaches have proved helpful at other complex monumental sites in the American Mid-South [105]. The aerial datasets we assessed included historic aerial photographs and LiDAR-derived visualizations we produced for the western edge of the Grand Plaza.…”
Section: Methods and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach to the survey area was explicitly multi-scalar and multi-method, with hopes of being able to disentangle some of the palimpsestic [102][103][104] evidence for social change at Cahokia. Such approaches have proved helpful at other complex monumental sites in the American Mid-South [105]. The aerial datasets we assessed included historic aerial photographs and LiDAR-derived visualizations we produced for the western edge of the Grand Plaza.…”
Section: Methods and Analysesmentioning
confidence: 99%
“…We used the DTM to produce additional analytical raster layers in the Relief Visualization Toolbox (RVT) v. 2.2.1 [108,109] with the hope that a diversity of visualizations would allow us to identify subtle topographic features (sensu, [92]). Blended images such as those described in Henry et al [105] were also produced from individual RVT visualization layers. Recent statistical analyses performed on imagery from a subsurface magnetic survey at Cahokia's Spring Lake Tract by Baires and colleagues [112] demonstrated that length:width ratios (L:W) can be compared across buildings of known size (determined from previous excavations) with those identified in gradiometry data to help tease apart We produced and assessed several of the visualizations in the RVT using the DTM, but we focus here on presenting the results of the sky-view factor (SVF) and positive openness.…”
Section: Lidar-derived Surface Visualizationsmentioning
confidence: 99%
“…However, the real advantages lie in the ability to generate DTMs for further analysis and in the classification of certain types of archaeological standing objects as buildings. The latter is particularly useful, for example, in a situation where standing objects are ubiquitous and modern buildings are absent, e.g., [87][88][89][90][91]. In such morphological contexts, the proposed pipeline (with possible tweaks to the settings) can be used for automatic feature detection at the point cloud level, which has many advantages.…”
Section: Automatic Ground Point and Object-type Classificationmentioning
confidence: 99%
“…Geophysical survey and mapping have become standard in the practice of archaeology to help answer anthropological and social–historical questions directly (Conyers & Leckebusch, 2010; Horsley et al, 2014; Locker et al, 2015; Stumpf et al, 2021; Thompson et al, 2011) and minimize the impact to unique and sensitive historical and archaeological remains. Over the past decade, geophysics has proved to be a useful methodology for mapping Woodland era villages and central places in the eastern United States (Bigman & Seinfeld, 2017; Birch & Lulewicz, 2014; Green et al, 2021; Henry, 2011; Henry et al, 2014; Henry et al, 2020; Horsley et al, 2014; King et al, 2017; McKinnon & Haley, 2017; Pluckhahn et al, 2010; Royce, 2011; Thompson & Pluckhahn, 2010; Wright, 2014) generally with the goal of delineating physical community organization and selecting locations for future excavations. Monumental architecture has also been extensively investigated across the area with various geophysical and remote sensing methods (Bigman & Lanzarone, 2014; Brannan & Bigman, 2014; Burks & Cook, 2011; Garrison, 1998; Green et al, 2021; Haley, 2014; Hargrave, 2011; Henry et al, 2020; Herrmann et al, 2014; Kassabaum et al, 2014; King et al, 2011; Schurr et al, 2020; Seinfeld et al, 2015; Thompson & Pluckhahn, 2010; Welch et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, geophysics has proved to be a useful methodology for mapping Woodland era villages and central places in the eastern United States (Bigman & Seinfeld, 2017; Birch & Lulewicz, 2014; Green et al, 2021; Henry, 2011; Henry et al, 2014; Henry et al, 2020; Horsley et al, 2014; King et al, 2017; McKinnon & Haley, 2017; Pluckhahn et al, 2010; Royce, 2011; Thompson & Pluckhahn, 2010; Wright, 2014) generally with the goal of delineating physical community organization and selecting locations for future excavations. Monumental architecture has also been extensively investigated across the area with various geophysical and remote sensing methods (Bigman & Lanzarone, 2014; Brannan & Bigman, 2014; Burks & Cook, 2011; Garrison, 1998; Green et al, 2021; Haley, 2014; Hargrave, 2011; Henry et al, 2020; Herrmann et al, 2014; Kassabaum et al, 2014; King et al, 2011; Schurr et al, 2020; Seinfeld et al, 2015; Thompson & Pluckhahn, 2010; Welch et al, 2005). These have provided the archaeological community with a good record of expectations for responses from mound construction layers and architectural features.…”
Section: Introductionmentioning
confidence: 99%